The coward - Aryan, Stephen, 1977- (Angry Robot, 2021)
"Ten years have passed, Kell lives a quiet farmer's life, while stories about his heroism are told in every tavern across the length and breadth of the land. But now a new terror has arisen in the north...For the second time, Kell is called upon to take up his famous sword, Slayer, and battle the forces of darkness. But he has a terrible secret that nobody knows. He's not a hero - he was just lucky"--